Finance and Development, December 1964. (Finance and Development; Finance and Development ;, 1964)
This paper presents highlights of the 1964 annual meetings of the IMF and the International Bank for Reconstruction and Development. The paper underscores that the charters of these organizations provide that they shall hold annual meetings of their Governors, who constitute the highest authority of each body. Although there are two principal institutions involved, and the special business of each is transacted separately, their annual meetings have always been held at the same time, and these joint meetings are in many respects a single and unified event.